Compressive strength and heavy metal adsorption of cork residue, natural zeolite, and low-grade metakaolin-based geopolymers. (22nd February 2023) - Sudagar, Alcina Johnson; Andrejkovičová, Slavka; Rocha, Fernando; Patinha, Carla; Velosa, Ana; da Silva, Eduardo Ferreira
Highlights: Crystallinity of the geopolymers increased with increasing zeolite in formulation. The addition of cork residue resulted in compact geopolymer materials. Maximum compressive strength of 26.7 MPa was obtained for the geopolymers. The geopolymers adsorbed in the order Pb 2+ > Cd 2+ > Cu 2+ > Zn 2+ > Cr 3+ . Portuguese metakaolins can be effective replacements for commercial metakaolin. Abstract: Low-grade Portuguese metakaolin (MK), natural zeolite and waste cork residue were tested as replacements for commercial MK-based geopolymers in terms of compressive strengths and heavy metal adsorption properties. The low-grade kaolins were sourced from the Alvarães (A) and Barqueiros (B) deposits in Portugal. Various sets of geopolymers were obtained by replacing MK with up to 75 wt% zeolite and adding cork residue, 20 wt% of the total powder mass, to all geopolymers (A25-C, B25-C – 25 % MK 75 % zeolite; A50-C, B50-C – 50 % MK 50 % zeolite; A75-C, B75-C − 75 % MK 25 % zeolite; A100-C, B100-C – 100 % MK). To keep the environmental footprint of the chemicals to a minimum, the Na2 O/Al2 O3 and SiO2 /Al2 O3 molar ratios were kept at 1. Geopolymers were characterized to understand the influence of different ratios of MK and zeolite and also cork residue incorporation on their structure and surface morphology. The crystallinity of the geopolymers increased with increasing zeolite in the structure. The addition of cork residue appeared to yield compact geopolymer materials. Maximum compressive strengths of 26.7 and 25.3 MPa were obtained for Alvarães and Barqueiros MK geopolymers, respectively, with only MK and cork residue in the structure, indicating that zeolite addition does not improve the compressive strength values. The adsorption of divalent Pb 2+, Cd 2+, Cu 2+ and Zn 2+ cations and the trivalent Cr 3+ cation indicated high adsorption capacities of Portuguese MK-based geopolymers. The adsorption of the cations is dependent on the composition of the geopolymers yielding selective adsorption. The geopolymers adsorb Pb 2+ in the highest amounts followed by Cd 2+ and Cu 2+ . Zn 2+ is adsorbed in slightly lower amounts and Cr 3+ is adsorbed in the least amounts. The cork residue and zeolite appear to significantly affect the structure, morphology and properties of geopolymers Overall, the Portuguese MK geopolymers containing cork residue can be effective replacements for commercial MK geopolymers.